Material Removal Rate and Surface Roughness on Grinding of Ductile Cast Iron Using Minimum Quantity Lubrication - M. M., Rahman; K., Kadirgama; M. M., Noor (Universiti Malaysia Pahang, 2015)
A promising alternative to conventional fluid coolant application is minimum quantity lubrication (MQL). Despite much research, there have been few investigations about the influence of MQL parameters on the process results, such as oil flow rate, workpiece speed and depth of cut. The objective of this project is to develop a mathematical model of the material removal rate and surface roughness on grinding of ductile cast iron using minimum quantity lubrication. The experiment was carried out according to the design of experiment principle, prepared based on central composite design. The experimental data was utilized to develop the mathematical model for first- and second-order models. The second order gives acceptable performance of the grinding. The result shows that the highest value of the grinding ratio is with single-pass MQL, and the lowest value is with multiple-pass conventional coolants. The model fit was adequate and acceptable for sustainable grinding using a 0.15% volume concentration of ethylene glycol. This paper quantifies the impact of water-based ethylene glycol on the surface quality achieved. It is concluded that the surface quality is most influenced by the depth of cut and table speed. It is recommended that future research is also conducted using another parameter such as the speed of the grinding wheel or the distance from the wheel–workpiece contact zone. Besides that, further research can be conducted using different nozzle angles and different types of grinding wheel to see how these affect the surface of the material.